Nearshore Larval Retention and Cross-Shelf Migration of Benthic Crustaceans at an Upwelling Center - Morgan, Steven G.; Miller, Seth H.; Robart, Matt J.; Largier, John L. (Frontiers in Marine Science, 2018)
Planktonic larvae are thought to be very susceptible to offshore advection in upwelling regimes, increasing dispersal and decreasing recruitment. However, larvae of 42 species of nearshore benthic crustaceans primarily developed on the inner shelf at locations both in (98.5%) and away (99.8%) from a perennial upwelling center in the upwelling season of a recruitment-limited region characterized by persistent, strong, upwelling. During three cross-shelf cruises conducted at each location, larvae of 21 species remained on the inner shelf at both sites by occurring beneath seaward-flowing surface currents while larvae of other species migrated to midshelf (four species) or offshore (14 species) by initially developing near the surface. Postlarvae apparently returned to shore either deep in landward-flowing upwelled water or near the surface where behavior allows them to be transported shoreward by internal waves, diel wind cycles or wind relaxation events. Thus, recruitment limitation in upwelling regimes does not appear to be caused by larval mortality from offshore transport, requiring new research directions to advance our understanding of population dynamics, structure and connectivity.